Development of Local Wisdom Realistic Mathematics Education Based Students Activity Sheet on Students' Mathematics Problem Solving Ability - Elvin Ervi Ladona; Caswita Caswita; Alben Ambrita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The selection of Student Activity Sheets (LKPD) is carried out to direct students' independent learning to help them understand the learning material. With local wisdom RME-based LKPD, students have a relatively firm understanding of mathematical problems. The purpose of this study is to develop LKPD products based on Realistic Mathematical Education (RME) with local wisdom of DAM Raman and Capit Urang Metro tourism objects on KPK and FPB materials that are suitable for use and are effective in mathematical problem-solving abilities. This type of research is research and development research and development (RnD) Borg and Gall. The population of this study was fourth-grade elementary/MI students in the Madrasah Working Group (KKM) 2 Metro City. The sampling technique used the class IV purposive sample technique at MINU Metro. The results of this study indicate that the development of RME-based LKPD products with local wisdom is declared feasible based on the results of validation from experts and is practical to use in terms of attractiveness, convenience, and usefulness. RME-based worksheets are effectively used in students' mathematical problem-solving abilities.